The microbiome of Total Suspended Particles and its influence on the respiratory microbiome of healthy office workers - Giulia Solazzo; Sabrina Rovelli; Simona Iodice; Matthew Chung; Michael Frimpong; Valentina Bollati; Luca Ferrari; Elodie Ghedin (Ecotoxicology and Environmental Safety)
Air particulate matter (PM) is widely recognized for its potential to negatively affect human health, including changes in the upper respiratory microbiome. However, research on PM-associated microbiota remains limited and mostly focused on PM (e.g., PM2.5 and PM10). This study aims to characterize for the first time the microbiome of Total Suspended Particles (TSP) and investigate the correlations of indoor TSP with the human upper respiratory microbiome. Biological and environmental samples were collected over three collection periods lasting three weeks each, between May and July 2022 at the University of Milan and the University of Insubria Como. TSP were sampled using a filter-based technique, while respiratory samples from both anterior nares (AN) and the nasopharynx (NP) were collected using swabs. Microbiome analysis of both human (N = 145) and TSP (N = 51) samples was conducted on metagenomic sequencing data. A comparison of indoor and outdoor TSP microbiomes revealed differences in microbial diversity and taxonomic composition. The indoor samples had higher relative abundance of environmental bacteria often associated with opportunistic infections like Paracoccus sp., as well as respiratory bacteria such as Staphylococcus aureus and Klebsiella pneumoniae. Additionally, both indoor and outdoor TSP samples contained broad spectrum antibiotic resistance genes. Indoor TSP exposure was negatively associated with commensal bacteria and positively associated with Staphylococcus aureus relative abundance. Finally, a correlation between the relative abundance of respiratory bacteria identified in the indoor TSP and the upper respiratory microbiome was found, suggesting a potential interaction between TSP and the upper airways.